Moving up a gear: The impact of compressing instructional time into fewer years of schooling - Mathias Huebener; Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Policy-makers face a trade-off between the provision of higher levels of schooling and earlier labour market entries. A fundamental education reform in Germany tackles this trade-off by reducing high school by one year while leaving the total instructional time unchanged. Employing administrative data on all high school graduates in 2002-2013 in Germany, we exploit both temporal and regional variation in the implementation of the reform and study the overall effectiveness of this reform. We find that compressing the high school track by one year reduces the mean high school graduation age by about 10 months. The probability to repeat a grade level in the course of high school increases by 21 percent (3 percentage points), peaking in the final three years before graduation. However, the high school graduation rate is not affected. The results indicate the reform's success in reducing the graduation age, though it stays behind its potential benefits for labour markets and social security schemes because of higher grade repetition rates.
Keywords: I28; J18; D04; 330; G12; G8; graduation age; grade repetition; grade retention; graduation rates; learning intensity; diff-in-diff; human capital; instructional time